CURRENT-TEMPERATURE ANALYSIS OF THE AMPACITY OF OVERHEAD CONDUCTORS DEPENDING ON APPLIED STANDARDS - Petrović, Ivica; Glavaš, Hrvoje; Hederić, Željko (Journal of Energy Technology, 2024)
The opening of the electricity market is accompanied by new market participants whose requirements need to be fulfilled in order for the electricity market to function. To do so, transmission capacity is of significant importance. As the building of new overhead lines is an expensive and long-term investment, increasing the transmission capacities of existing lines is an unavoidable necessity. The transmission capacity of overhead power lines is commonly determined by limitations on the conductor’s temperature, characterized by its ampacity. The conductor’s temperature, and therefore the ampacity, is dependent on weather conditions. This fact enables increasing the transmission capacity according to calculations based on current weather conditions and forecasts, as opposed to static and conservative values. This paper discusses the application of different standards and comparison of results for transmission capacity value, with particular reference to Croatian legislation on transmission overheadpower lines. Calculation of sensitivity on input parameters is also examined because of the changes in the weather that change transmission capacity. As an extreme case of unfavourable weather conditions, an example is given of transmission capacity value trends during the hottest recorded day Croatia. The conclusion is that increases of the transmission capacity on particular power lines is possible but, for the safe and secure operation of the transmission grid, a seasonal regime of operation or ampacity zones depending on the time of the year could be made.